The Role of Indonesia's G20 Presidency in Shaping Global Health Architecture After the Covid-19 Pandemic - Saepudin, Saepudin; Haryati , Vivit Widi; Revidy, Aldebaran Raihan; Audrei, Fanesya (Journal of International Relations on Energy Affairs, 2024)
The Covid-19 pandemic is a complex global problem because almost all countries in the world are not prepared to deal with it. This problem needs to be responded quickly through international cooperation forums. Therefore, this study aims to determine Indonesia's role through the G20 presidency in shaping resilient global health architecture for now and the future. This research uses descriptive-qualitative method with secondary data collection, from books, journal articles, reports of related institutions, and internet articles. Robert Keohane's theory of multilateralism and the concept of health diplomacy are the analytical tools used in this research. Indonesia's leadership in the G20 provides opportunity for Indonesia to bridge the gap in promoting equitable global vaccine access between countries in the northern and southern hemispheres through research collaboration. Furthermore, Indonesia also plays a role in encouraging harmonization of global health regulations and establishing the Pandemic Fund. This agreement provides opportunity for Indonesia to accommodate the interests of developing countries and demonstrate its opportunity for global leadership. Conversely, this agreement faced with uneven country capabilities and concerns that this commitment will not continue in the next presidency because it clashes with domestic interests of each country.